2015
DOI: 10.1183/09031936.00011815
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis ofMycobacterium abscessuscomplex infection in cystic fibrosis

Abstract: Early signs of pulmonary disease with Mycobacterium abscessus complex (MABSC) can be missed in patients with cystic fibrosis (CF). A serological method could help stratify patients according to risk. The objective of this study was to test the diagnostic accuracy of a novel method for investigating IgG activity against MABSC.A prospective study of all patients attending the Copenhagen CF Centre was conducted by culturing for MABSC during a 22-month period and then screening patients with an anti-MABSC IgG ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 36 publications
5
35
0
1
Order By: Relevance
“…The dotted horizontal line is at 125 ELISA Units (test positive threshold). Reproduced from with permission from the authors.…”
Section: Why Early Diagnosis Is Importantmentioning
confidence: 99%
See 1 more Smart Citation
“…The dotted horizontal line is at 125 ELISA Units (test positive threshold). Reproduced from with permission from the authors.…”
Section: Why Early Diagnosis Is Importantmentioning
confidence: 99%
“…Although, some have suggested that the majority of patients with CF and NTM are only transiently culture positive , this concept of airway colonization by NTM has never been tested rigorously . Our finding that MABSC exhibits biofilm growth and induces a humoral immune response , points more toward periods of latent infection than actual transient colonization. In patients fulfilling ATS criteria for pulmonary disease and where other competing causes have been ruled out, hesitation should be avoided.…”
Section: Eradicating Mabscmentioning
confidence: 99%
“…The dotted horizontal line is the 125 ELISA units (test positive threshold). The dotted vertical line represents the date of first positive culture (reproduced from .…”
Section: Cystic Fibrosis and Biofilm Infection – Pathogenetic And Diamentioning
confidence: 99%
“…62 To enhance detection of mycobacterial infection, patients attending the Copenhagen CF Centre were cultured for Mycobacterium abscessus (MABSC) and had an anti-MABSC IgG ELISA performed over 22 months. 63 Patients with MABSC pulmonary disease had median anti-MABSC IgG levels that were sixfold higher than patients with no history of infection (434 vs. 64 ELISA units; P < 0.001); test sensitivity was 95% and specificity was 73%. A study from France showed that chronic administration of azithromycin was protective against NTM infection in adults with CF, and suggested its use as primary prophylaxis.…”
Section: Respiratory Tract Infectionmentioning
confidence: 88%
“…A case report highlighted that non‐tuberculous mycobacteria (NTM), in this instance the Mycobacterium avium complex, may be the first organism of significance isolated from the CF lung . To enhance detection of mycobacterial infection, patients attending the Copenhagen CF Centre were cultured for Mycobacterium abscessus (MABSC) and had an anti‐MABSC IgG ELISA performed over 22 months . Patients with MABSC pulmonary disease had median anti‐MABSC IgG levels that were sixfold higher than patients with no history of infection (434 vs. 64 ELISA units; P < 0.001); test sensitivity was 95% and specificity was 73%.…”
Section: Respiratory Tract Infectionmentioning
confidence: 99%